Metabolic Effects of Cobalt Ferrite Nanoparticles on Cervical Carcinoma Cells and Nontumorigenic Keratinocytes - Bortolozo Oliveira, Ana Beatriz [UNESP]; Moraes, Fabio Rogerio de [UNESP]; Candido, Natalia Maria [UNESP]; Sampaio, Isabella [UNESP]; Paula, Alex Silva [UNESP]; Vasconcellos, Adrian de [UNESP]; Silva, Thais Cerqueira [UNESP]; Miller, Alex Henrique [UNESP]; Rahal, Paula [UNESP]; Nery, Jose Geraldo [UNESP]; Calmon, Martha Freitas [UNESP] (Amer Chemical Soc, 2016)
The cytotoxic response, cellular uptake, and metabolomic profile of HeLa and HaCaT cell lines treated with cobalt ferrite nanoparticles (CoFe2O4 NPs) were investigated in this study. Cell viability assays showed low cytotoxicity caused by the uptake of the nanoparticles at 2 mg/mL. However, metabolomics revealed that these nanoparticles impacted cell metabolism even when tested at a concentration that presented low cytotoxicity according to the cell viability assay. The two cell lines shared stress-related metabolic changes such as increase in alanine and creatine levels. A reduced level of fumarate was also observed in HeLa cells after treatment with the nanoparticles, and this alteration can inhibit tumorigenesis. Fumarate is considered to be an oncometabolite that can inhibit prolyl hydroxylase, and this inhibition stabilizes HIF1 alpha, one of the master regulators of tumorigenesis that promotes tumor growth and development. In summary, this study showed that nanoparticle-treated HeLa cells demonstrated decreased concentrations of metabolites associated with cell proliferation and tumor growth. The results clearly indicated that treatment with these nanoparticles might cause a perturbation in cellular metabolism.
Keywords: cobalt ferrite nanoparticles; cell lines; cytotoxicity; cell uptake; metabolomics